Feasibility study of using heat recovery devices in HVAC systems in a building in the tropics - Yau, Y.H.; Chuah, K.H.; Tey, M.R.; Yip, P.N.; Lim, C.S.; Chong, T.H.; Krishnan, R. (2014)
For non-domestic buildings, the electricity consumption mostly comes from the usage of the air-conditioning system. Therefore, energy savings must be achieved to save cost, and hence there is a need to apply heat recovery technologies such as run-around coils, plate-to-plate heat exchangers, heat pipe heat exchangers and heat recovery wheels into the air conditioning and mechanical ventilation (ACMV) systems for these buildings. The examples of non-domestics buildings such as factories, hospitals and office buildings use more energy to supply fresh air into the space in comparison to residential buildings. According to Yau (2010), the changing of air must be at least 15 times hourly, and in certain cases such as the hospital, the prohibition of recirculation of the return air in operating theatres to ensure the air is clean from any virus or bacteria from the outdoor air is needed. The feasibility study on using heat recovery devices in a new medium-size building in University of Malaya was conducted. The potential of energy savings in the building was examined by studying the performance of the air-conditioning system. The heat recovery systems were analyzed, and the focus was on the energy savings of the HVAC system. The calculation of energy savings and payback periods were analyzed for the chosen heat recovery devices installed in the building. Based on the results obtained in this practical study, it is strongly recommended that heat recovery systems to be installed to reduce energy usages of air-conditioning systems operating in large buildings in the tropics.